2009
DOI: 10.3858/emm.2009.41.4.030
|View full text |Cite
|
Sign up to set email alerts
|

Calcium overload is essential for the acceleration of staurosporine-induced cell death following neuronal differentiation in PC12 cells

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 33 publications
(39 reference statements)
0
23
0
Order By: Relevance
“…It was demonstrated that neurite outgrowth in PC12 by staurosporine is induced via the Ca 2+ -signal transduction pathway by the Ca 2+ infl uxes through endoplasmic reticulum channels. On the other hand, recent study showed that staurosporine leads to intracellular calcium overload, which induces apoptosis in PC12 cells (6). In the percent study, we showed that inhibition of IP3R and PLCγ caused a large increase in (Ca We reported previously that staurosporine can induce neurite outgrowth in PC12 cells and that this apoptosis can be blocked by reducing extracellular calcium stores (12).…”
Section: Discussionmentioning
confidence: 72%
“…It was demonstrated that neurite outgrowth in PC12 by staurosporine is induced via the Ca 2+ -signal transduction pathway by the Ca 2+ infl uxes through endoplasmic reticulum channels. On the other hand, recent study showed that staurosporine leads to intracellular calcium overload, which induces apoptosis in PC12 cells (6). In the percent study, we showed that inhibition of IP3R and PLCγ caused a large increase in (Ca We reported previously that staurosporine can induce neurite outgrowth in PC12 cells and that this apoptosis can be blocked by reducing extracellular calcium stores (12).…”
Section: Discussionmentioning
confidence: 72%
“…homeostasis of differentiated PC12 cells. Seo and Seo [59] found that the anti-apoptotic Bcl-2 family member Bcl-X L prevented STS-induced neuronal cell death by interfering with Ca 2? -mediated apoptotic signals by inhibiting Ca 2?…”
Section: Discussionmentioning
confidence: 99%
“…Many important mechanisms involved in apoptosis have been determined using STS or mycotoxin, a general protein kinase inhibitor that triggers apoptosis in model cell lines (Xia et al, 1995;Jacobsen et al, 1996;Seo and Seo, 2009). The intracellular signaling of STS induced apoptosis is dependent on cell type.…”
Section: Staurosporine (Sts) Induces Neuronal Apoptosis In H19-7 Cellmentioning
confidence: 99%